اثر أنموذج ثيلين في اكتساب المفاهيم التاريخية لطالبات الصف الثاني معهد المعلمات / المركزي في مادة التاريخ (Journal Of Educational and Psychological Researches, 2012)
Chapter One – introduction Nations managed today to achieve progress in the field of modern technology. Science has changed many beliefs and trendiness that people have held for long time, skills and scientific thinking developed, and made scientific observation  and experiment replace narration and taking from others. That is attributed to examining  the educational systems searching for the locations of defect, and shortage.In the light of educational modernizations, many models of teaching incliuding a model for social tracing attributed to Herbart Thelen, which is a model to develop skills of social participation in the democratic process (Al-Khawalda,1993,335). Thelen cared for the basis of democracy as a base of building social relations and social relationships between the various individuals. He supposed that the model could be achieved through the education process within the democratic process as the social unit (Qatami, 1998, 246).Thelen Model of social investigation is model of teaching that is based on the development of educational system through democratic procedures, especially when it is used in teaching the social items. That would develop positive participations and interaction among students and contribute to the increasing of their acquisition and training to the use of teaching strategies that help to use strategies that motivate their thinking (Abdullah, 1998,71).The importance of group investigation of Thelen model is manifested in the teaching as a method of making students think of the dimensions of the lesson and its contents, and give them the space to express their opinions in a democratic and practical manner (Sharpes.p.3,1983). The study of concepts lead to increase the student's ability to the use of the main functions of science which is implied in evaluation and prediction. For the meaning of historical concepts and is constructed in the required context that should take the mental age and living expertise into consideration. The second chapter: The chapter included a review of the previous Arab and foreign studies in two domains:The first: tackling the Arab and foreign studies of Thelen model of investigation. The second: tackling Arab and foreign studies about the historical terms. The third: procedures of study:The Sample: the sample of study included two groups (experimental and control). The number of stundets were 26 female students of the experimental and 27for the control group after eliminating the failing students. The researcher matched the two groups in terms of:Scores of history for the year 2006 / 2007.IQ test Pervious knowledge test. The Tools of study:prepared a test to acquire the historical concepts of the multi choice type made up of (40) items, which she displayed to experts and specialized, and she derived the coefficient of difficulty. The experiment lasted for two months.Statistical Instrument of study:The researcher used statistical means such as T-test, Spearman – Braun equation. The results: The results showed significant differences between the experimental group and control group which were taught using Thelen model.The researcher attributed that excellence to the methods of teaching used based on dialogue and discussion and exchange opinions over the traditional methods. That is attributed to the traditional methods of teaching that keeps with the informational development in the world and promote activity, seriousness and vividness to contribute to elevate the level of students and increase their acquisition of historical concepts and then retain those information.The most important conclusions were:• The use of Thelen Model of group investigation depends on the activity and cooperation of students in inquiring and seeking information in essence. • The probability of applying Thelen Model of group investigation in teaching history of second stage students in the teacher's institute. • That requires the availability of efficiencies and skills by teachers. In the light of these results, the researcher recommends to:• Arrange development courses by Ministry of Education for teachers of history of how to use methods of teaching which focus on thelearner as the center of activity in the teaching process. • Use Thelen Model of group investigation as an effective means within the methods of teaching in the history curricula in colleges and institutes. The suggestions were: • Making similar studies for other stages on both sexes to know the effect of Thelen Model of group investigation in acquiring historical concepts. • The study of Thelen Model of group investigation in other variables like achievement or thinking of its types.